Perancangan Interior ‘LOTS’ Edutainment Center di Surabaya - Laurencia Nathalia Susanto; Hedy Constancia Indrani; Grace Setiati Kattu (Intra, 2019)
In this modern era, children have started to feel bored studying in a formal situation. Besides, life now has entered a digital era and technology has advanced majorly. These technology advances can be applied on various kinds of children’s games and can ata the same time give knowledge which is use full for childre’s development. ‘LOTS’ Edutainment Center, with its seaworld concept, is designed to be an alternative playground and study space outside formal institution for children aged 3-12 years old in Surabaya. Through the technologically-supported sensory approach, this can also be a place for children to do their activities and a place to later improve children’s development. The design methodology used is design thinking with stages, namely, (1) Understand, (2) Observe, (3) Point of View, (4) Ideate, (5) Prototype, (6) Test, (7) Storytelling, (8) business Model. The supporting facilities of this edutainment center include an educative playground area which is divided into 8 parts and gelato cafe.